Wykluczenie finansowe i integracja finansowa – aspekty terminologiczne - Czarnecka, Maria (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2018)
The aim of the article was to present the issue of financial exclusion and define sensitive areas of this phenomenon. The factors that may be relevant for measuring the degree of financial exclusion were analysed. An attempt was also made to determine the difficulties in access to financial services in the context of practices applied by both the supply and demand sides. In addition, barriers to the use of services were analysed as were financial products in terms of practices used by supply and demand. The typology of financial exclusion presented in the article is an attempt to define the type and scope of the phenomenon. Bank exclusion, credit exclusion and exclusion from the savings system are financial exclusion indicators. Each of those types of exclusion affects the economic and social level. Financial exclusion, which is one of the symptoms of the imbalance between demand and supply, is understood here as total or partial access to financial services offered by the market. The article also attempts to analyse the causes of exclusion with the division into supply and demand factors. The typology of financial exclusion proposed in the article may be a contributing factor to the reverse phenomenon, which is financial inclusion.